Use of essential oils for ADHD treatment - Simões , Deise Vimaana Santos de Souza; de Freitas , João Fábio; Alves, Kemeli Marcela Nagayoshi (Seven Editora, 2024)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurobehavioral condition that affects both children and adults, with a significant prevalence. Traditionally, treatment involves behavioral therapy and medications, such as stimulants. However, research has explored the use of essential oils as an alternative approach. This review analyzes recent studies on the effects, applications, and mechanisms of essential oils in the treatment of ADHD, considering their efficacy, limitations, and safety issues. Essential oils show potential due to their soothing properties. This review contributes to the understanding of essential oils in the management of ADHD and their impact on the quality of life of those affected. DOI:https://doi.org/10.56238/sevened2024.026-031